Coexistence barriers confine the poleward range of a globally distributed plant. (6th October 2020) - Armitage, David W.; Jones, Stuart E.
Abstract: In the study of factors shaping species' poleward range boundaries, climatic constraints are often assigned greater importance than biotic interactions such as competition. However, theory suggests competition can truncate a species' fundamental niche in harsh environments. We test this by challenging a mechanistic niche model – containing explicit competition terms – to predict the poleward range boundaries of two globally distributed, ecologically similar aquatic plant species. Mechanistic competition models accurately predicted the northern range limits of our study species, outperforming competition‐free mechanistic models and matching the predictive ability of statistical niche models fit to occurrence records. Using the framework of modern coexistence theory, we found that relative nonlinearity in competitors' responses to temperature fluctuations maintains their coexistence boundary, highlighting the importance of this fluctuation‐dependent mechanism. Our results support a more nuanced, interactive role of climate and competition in determining range boundaries, and illustrate a practical, process‐based approach to understanding the determinants of range limits. Abstract : Species' poleward ranges are commonly thought to be limited by climatic constraints rather than by competition. We test this prediction by challenging a mechanistic niche model that includes interspecific competition terms to predict the range limits of two globally‐distributed plant species. Our results suggest that competition between the species at high latitudes leads to a coexistence boundary that limits the inferior competitor's further poleward expansion.